Colorado Front Range GK12 connecting kids and ecology — teachers and researchers - Seemueller, Carol, author; Quirk, Meghan H., author; Moore, John C., author; Hartley, Laurel M., author; SGS-LTER, Colorado State University, publisher (Colorado State University. Libraries, 2005)
The Colorado Front Range GK12 project is a collaborative effort of Colorado State University, the University of Northern Colorado, Weld County School District 6, and Poudre School District.
The SGS-LTER research site was established in 1980 by researchers at Colorado State University as part of a network of long-term research sites within the US LTER Network, supported by the National Science Foundation. Scientists within the Natural Resource Ecology Lab, Department of Forest and Rangeland Stewardship, Department of Soil and Crop Sciences, and Biology Department at CSU, California State Fullerton, USDA Agricultural Research Service, University of Northern Colorado, and the University of Wyoming, among others, have contributed to our understanding of the structure and functions of the shortgrass steppe and other diverse ecosystems across the network while maintaining a common mission and sharing expertise, data and infrastructure.
Colorado State University. Natural Resource Ecology Laboratory; Colorado State University. Department of Forest and Rangeland Stewardship; Colorado State University. Department of Soil and Crop Sciences; Colorado State University. Department of Biology; California State University, Fullerton; United States. Agricultural Research Service; University of Northern Colorado; Rocky Mountain High School.
Keywords: long term ecological research; Central Plains Experimental Range; Pawnee National Grassland; grassland ecology; shortgrass steppe